CERN. Multiscalar Paradigm - Luigi Mandraccio (Agathón)
The multiscalar issue is interpreted here as an essential principle of the mechanics of the project. Each scale, even if taken individually, must be considered within a reference system that is coherent not only based on a series of quantitative and conventional starting principles but even more than a general logic composed of the totality of the scales involved. The contribution – focused on the structures of the European Organization for Nuclear Research (CERN) in Meyrin – aims to investigate the issue of ‘scales’ by looking at the multiscalar project as a creator of a ‘difficult unit’, composed through a ‘structure’ «[… ] as to how things become intelligible» (Forty, 2012, p. 283). CERN, an extraordinary inescapable machine, represents a paradigmatic case on the issue of the multiscalar project.